From copper homeostasis to cuproptosis: a new perspective on CNS immune regulation and neurodegenerative diseases - Li, Luhao; Lv, Liangzhen; Wang, Zhaodi; Liu, Xianbao; Wang, Qingyi; Zhu, Hui; Jiang, Bei; Han, Yapeng; Pan, Xue; Zhou, Xueming; Ren, Li; Chang, Zhuo (Frontiers in Neurology, 2025)
Copper, an essential trace element for the human body, plays a key role in energy metabolism, mitochondrial respiration, redox reactions, and neural signal transmission. The recently proposed concept of “cuproptosis” has further revealed the unique status of copper in cellular regulation: when copper abnormally accumulates within cells, it can directly bind to the lipoylated proteins of the mitochondrial TCA cycle, triggering protein aggregation and metabolic disorders, ultimately leading to cell death. This form of cell death plays an important role in various neurodegenerative diseases of the central nervous system, such as Alzheimer’s disease (AD), Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS), Huntington’s disease (HD), and stroke. This review summarizes recent research on the mechanisms of cuproptosis, providing new perspectives and a theoretical basis for understanding the pathogenesis of these neurodegenerative diseases.